Integrated network pharmacology reveals the mechanism of action of Xianlinggubao prescription for inflammation in osteoarthritis - Jingyi Hou; Yubo Li; Yu Zhang; Ning Yang; Bin Chen; Guiyun Ma; Naiqiang Zhu (BMC Complementary Medicine and Therapies)
Abstract Background Osteoarthritis (OA), a leading cause of disability worldwide, is characterized by complex interactions between cartilage degradation and synovial inflammation. While NSAIDs are the primary treatment, their prolonged use exacerbates gastrointestinal risks and does not alter disease progression. Xianlinggubao (XLGB), an approved Chinese herbal remedy for osteoporosis, has demonstrated promising anti-osteoarthritic effects in preliminary studies. However, its multi-component mechanisms targeting OA-related inflammation require further clarification. This study integrates network pharmacology with experimental validation to investigate XLGB's anti-inflammatory mechanisms in OA. Methods Bioactive compounds of XLGB and their respective targets were sourced from the TCMSP, ETCM, SymMap, and ChEMBL databases. Targets linked to OA-related inflammation were identified through differential expression analysis and by querying OMIM, GeneCards, and PubMed Gene databases. Network pharmacology and bioinformatics approaches were employed to construct compound-target and protein–protein interaction (PPI) networks, enabling the identification of pivotal therapeutic targets. Functional enrichment of these targets was performed using the ClusterProfiler package in R. The binding affinity of compounds to anti-inflammatory OA targets was assessed through molecular docking, dynamics simulations, RT-PCR, and immunofluorescence assays. Results Fifty-five bioactive compounds corresponding to 475 XLGB targets and 125 genes involved in OA-related inflammation were identified. PPI network analysis revealed that XLGB may alleviate OA inflammation by modulating key genes, including COX-2, IL-1β, TNF, IL-6, and MMP-9. Molecular simulations indicated strong binding affinities between bioactive compounds in XLGB and these critical targets. Functional enrichment analysis suggested that XLGB's anti-inflammatory action in OA may involve regulation of pathways such as IL-17, TNF, and NF-κB. In vitro experiments further confirmed that XLGB mitigates OA inflammation by modulating these genes, proteins, and signaling pathways. Conclusions Through network pharmacology, this study elucidated the mechanisms of XLGB in OA inflammation, highlighting its modulation of IL-6, IL-1β, TNF-α, PTGS2, MMP-9, and the NF-κB pathway. These findings provide strong support for the clinical application of XLGB in managing OA-related inflammation.